1995
DOI: 10.1007/bf00191212
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta localization during mouse prostate morphogenesis and in prostatic growth abnormalities

Abstract: Growth and morphogenesis of the prostate involves mesenchymal-epithelial interactions. Transforming growth factor-beta 1 (TGF-beta1) is one growth factor that may play a role in these paracrine interactions. We have localized TGF-beta1 by molecular and immunohistochemical analysis in the developing mouse prostate. Accumulations of TGF-beta1 protein were localized in the mesenchyme surrounding ductules in fetal and neonatal prostate. Previous studies in the mouse prostate reconstitution (MPR) model system have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…The present study demonstrated higher TGF␤1 stain- ing in malignant epithelial glands, and the staining was intracellular. Since the antibody we used recognizes the latency-associated protein, our data and those of Timme et al [11] and Truong et al [12] suggest that prostate cancer epithelial cells have both increased intracellular latent TGF␤1 (LAP-TGF␤1) and extracellular active mature TGF␤1 (CC TGF␤1 ab) forms. As malignant prostate cancer cells are able to activate latent TGF␤1, the extracellular TGF␤1 protein observed with the CC antibody may represent malignant prostate-activated TGF␤1 protein [13].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The present study demonstrated higher TGF␤1 stain- ing in malignant epithelial glands, and the staining was intracellular. Since the antibody we used recognizes the latency-associated protein, our data and those of Timme et al [11] and Truong et al [12] suggest that prostate cancer epithelial cells have both increased intracellular latent TGF␤1 (LAP-TGF␤1) and extracellular active mature TGF␤1 (CC TGF␤1 ab) forms. As malignant prostate cancer cells are able to activate latent TGF␤1, the extracellular TGF␤1 protein observed with the CC antibody may represent malignant prostate-activated TGF␤1 protein [13].…”
Section: Discussionsupporting
confidence: 57%
“…Eklov et al [10] have shown increased TGF␤1 epithelial intracellular immunoreactivity in formalin-fixed human prostate cancer sections using TGF␤1 antibody specific for TGF␤1 peptides 78-109. Timme et al [11] and Truong et al [12] have demonstrated that the CC TGF␤1 antibody, which recognizes the N-terminal 30 amino acids of the extracellular form of TGF␤1, is increased around malignant epithelial cells. In contrast, the LC TGF␤1 antibody which is specific for the N-terminal 30 amino acids of the intracellular form of TGF␤1 is unchanged in prostate cancer [11,12].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Transforming growth factor-␤ (TGF-␤) is a growth factor which is capable of inhibiting prostate cell growth in vitro [3][4][5][6], and has apparent prostate cell growth regulatory roles in vivo [7][8][9][10]11]. In fact, early loss of responsiveness to TGF-␤-mediated growth inhibition has been associated with clinical progression of prostate cancer [10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is unclear whether the classical pro-angiogenic factors are important in regulating angiogenesis in BPH due to these inconsistent findings. Intriguingly, previous studies have shown that inflammatory factors including IL-1, IL-8, TGFb were capable to mediate angiogenesis in addition to their typical inflammatory functions and more importantly, these factors were highly expressed in some cases of BPH tissues with inflammation [40,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Given that angiogenesis is a typical vascular response to inflammation and prostatic inflammation is a common feature in BPH, it is tempting to speculate that prostatic inflammation in BPH induces vascular remodeling through the angiogenic effects of the inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%